Internalisation of Entrepreneurial Character through Augmented Reality Integrated Biopreneurship Learning for Students - Akhmad Kurnia; Lutfi Lutfi; Risma Haris (DIDAKTIKA, 2025)
The development of entrepreneurial values is not only at the level of introduction but must also require real practice in students' daily lives so that efforts are needed to internalise entrepreneurial character in students. Therefore, the writing of this article aims to internalise entrepreneurial character through augmented reality integrated biopreneurship learning. The writing of this article uses a systematic review method based on several references in the form of books and articles as well as online scientific publications. The conclusion of this article is that internalising the entrepreneurial character of students through biopreneurship learning using augmented reality allows for more interactive learning and provides a deeper and more contextual understanding for students.